Residência multiprofissional em saúde da família e comunidade: um olhar sobre a multiprofissionalidade na atenção básica - Salvador, Anarita de Souza (2010)
The constant quest for realization of the right to health care is experienced by many professionals that guide their work practices through the blueprint of the SUS. The practice has demonstrated multi-configure itself as an important strategy to guarantee the principle of comprehensiveness. That is to enable the user of SUS means necessary so that they get full assistance it requires, at all levels of system complexity and scope of his life. The training of professionals committed to the NHS and prepared to actualize new knowledge and technologies in this system has become vital to maintaining that system. The present study examined the process of forming the Multidisciplinary Residency in Family and Community Health, linked to the Center for Public Health Research at the Federal University of Paraíba, trying to analyze how residents are experiencing a multidisciplinary practice in primary care and multidisciplinary practices which are being constructed in the process of formation. It was a field research, exploratory, with a theoretical foundation of the Marxist dialectic, conducted through literature search and questionnaire distributed to residents of the professional program available. We conclude that the RMSFC emerged as a privileged space for building new multi-practice interventions that are helping to change attitudes of professionals and consolidating multiprofessionality while a new strategic direction of the work process in health services, especially the health units of the family which residents are inserted.